The Influence of Mind Mapping Technique and Students’ Attitude toward Students’ Ability in Writing a Recount Text of the Eighth Grade Students of State Junior High School 45 Palembang - Arie Firmansyah (RIPTEKSI KEPENDIDIKAN PGRI, 2013)
AbstractThe Research is title The Influence of mind mapping technique and students’ attitude toward the students’ ability in writing a recount text the First year students of SMPN 45 Palembang. The findings of the study showed that: (1) there was a significant difference in average score of writing a recount text between the positive and negative students’ attitude who were taught using mind mapping technique, indicated by p-output (0.002).(2) there was a significant difference in average score of writing a recount text between the positive and negative students’ attitude who were taught using conventional strategy, indicated by p-output (0.003). (3) there was a significant difference in average score of writing a recount text between the positive students’ attitude who were taught using mind mapping technique and those who were taught using conventional strategy, indicated by p-output (0.000). Therefore, it can be concluded that Mind Mapping Technique improved students’ writing achievement. Keywords: Mind Mapping Technique, Students’ Attitude, Students’ Ability